A.K. Chesterton and the evolution of Britain's extreme right, 1933-1973 - LeCras, Luke (Routledge studies in fascism and the far right, 2020)
Born in war : life before politics, 1899-1933 -- The Blackshirt life : the British Union of Fascists, 1933-1938 -- My country right and wrong : fascism after Mosley, 1938-1939 -- Drawing room fascism : the After-Victory Group, 1943, 1946 -- Sound the alarm : Candour and the League of Empire Loyalists, 1953-1967 -- Forward to extremists : the National Front, 1967-1973 -- What is behind it all? Racism, anti-Semitism and conspiracy after 1945.